Sabina FL: A new rice variety with improved yield potential in Dominican Republic - CGIAR Research Program on Rice (2021)
Certified seeds from Sabina FL are already being used by rice farmers in this country. Currently, this variety is in its first stages of seed production looking forward to a massive adoption by farmers over the next two to three years.